Comprehensive gas chromatography–electron ionisation mass spectrometric analysis of fatty acids and sterols using sequential one‐pot silylation: quantification and isotopologue analysis. (22nd May 2014) - Kloos, Dick‐Paul; Gay, Emmanuel; Lingeman, Henk; Bracher, Franz; Müller, Christoph; Mayboroda, Oleg A; Deelder, André M; Niessen, Wilfried M A; Giera, Martin
<x xml:space="preserve">Abstract</x> RATIONALE Fatty acids and sterol lipids play crucial roles in several biological processes and several biological facts underline the interconnection between these lipid classes. Therefore, it is of interest to develop a comprehensive method analysing both classes in the form of their most favourable derivatives suitable for quantification and isotopologue analysis. METHODS Lipids were derivatised by a sequential one‐pot procedure using N‐tert‐butyldimethylsilyl‐N‐methyltrifluoroacetamide (MtBSTFA) and N, O‐bis(trimethylsilyl)trifluoroacetamide (BSTFA). No clean‐up or concentration steps were necessary. The prepared samples were directly available for gas chromatography–electron ionisation mass spectrometric (GC–EI‐MS) analysis on a standard column. For quantification, the SIM mode was used and for isotopologue analysis scheduled scan mode was applied. RESULTS Development of a sequential one‐pot derivatisation for GC–EI‐MS allowing comprehensive analysis of fatty acids and sterols as their most favourable derivatives. Validation carried out using human plasma, comparison with certified NIST plasma. LLOQ of usually 3.3 ng/mL achieved. Isotopologue analysis of 2‐[13C]‐acetate incorporation in HL‐60 cells proving feasibility of method. CONCLUSIONS The presented method successfully combines two consecutive silylation reactions in one pot, enabling the analysis of both fatty acids and sterols in a comprehensive analytical method. The method has great potential for the quantification of lipids as well as the comprehensive study of both biochemical pathways, using [13C]‐flux analysis. Copyright © 2014 John Wiley & Sons, Ltd.